Protein losing enteropathy secondary to a pulmonary artery stent - Narayanswami Sreeram; Uwe Trieschmann; Gerardus Bennink (Wolters Kluwer Medknow Publications, 2012)
A 2-year-old patient with hypoplastic left heart syndrome presented 6 months following Fontan completion with protein-losing enteropathy (PLE). He had undergone stent implantation in the left pulmonary artery after the Norwood procedure, followed by redilation of the stent prior to Fontan completion. Combined bronchoscopic and catheterization studies during spontaneous breathing confirmed left bronchial stenosis behind the stent, and diastolic systemic ventricular pressure during expiration of 25 mm Hg. We postulate that the stent acts as a valve, against which the patient generates high expiratory pressures, which are reflected in the ventricular diastolic pressure. This may be the cause of PLE.